2019
DOI: 10.7554/elife.47015
|View full text |Cite
|
Sign up to set email alerts
|

B cell receptor and Toll-like receptor signaling coordinate to control distinct B-1 responses to both self and the microbiota

Abstract: B-1a cells play an important role in mediating tissue homeostasis and protecting against infections. They are the main producers of ‘natural’ IgM, spontaneously secreted serum antibodies predominately reactive to self antigens, like phosphatidylcholine (PtC), or antigens expressed by the intestinal microbiota. The mechanisms that regulate the B-1a immunoglobulin (Ig) repertoire and their antibody secretion remain poorly understood. Here, we use a novel reporter mouse to demonstrate that production of self- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 70 publications
4
55
0
Order By: Relevance
“…B1a cells of Nfkbiedeficient mice show a significant downregulation of IgM expression in peritoneal B1a cells, with respect to WT and presented two B220lowCD19+CD5+B1a populations with different levels of IgM expression (B1a IgMhi and B1a IgMlow). Nfkbie −/− B1a IgMlow population showed impaired proliferation response to TLRs stimuli and reduced ex vivo survival compared to B1a IgMhi cells, in agreement with the key role of BCR in B1 cells expansion and activation 28,30,[45][46][47][48][49] . Downregulation of IgM on B cells contributes to a physiological B-cell immune tolerance mechanism called anergy, and serves to restrain their response to endogenous/self-antigens and to chronic BCR stimulation 50 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…B1a cells of Nfkbiedeficient mice show a significant downregulation of IgM expression in peritoneal B1a cells, with respect to WT and presented two B220lowCD19+CD5+B1a populations with different levels of IgM expression (B1a IgMhi and B1a IgMlow). Nfkbie −/− B1a IgMlow population showed impaired proliferation response to TLRs stimuli and reduced ex vivo survival compared to B1a IgMhi cells, in agreement with the key role of BCR in B1 cells expansion and activation 28,30,[45][46][47][48][49] . Downregulation of IgM on B cells contributes to a physiological B-cell immune tolerance mechanism called anergy, and serves to restrain their response to endogenous/self-antigens and to chronic BCR stimulation 50 .…”
Section: Discussionsupporting
confidence: 76%
“…BCR signaling plays an instructive role in B1a cell lineage determination and maintenance 28,30,44,45 . In addition, recent studies showed that BCR signaling cooperates with TLR signaling in controlling expansion and activation of B1a B cells [46][47][48][49] . NF-κB is one of the key transcription factors activated by BCR and TLR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…B1 cells are selected for autoreactivity and form a pool of long-lived, self-renewing B cells that produce the majority of circulating, naturally occurring, low-affinity IgM and IgG, that cross-react with both autoantigens and conservative microbial antigens. According to recent data, Toll-like receptors (TLR)-mediated activation of B1 cells through CpG oligonucleotides, or lipopolysaccharides, leads to a rapid increase in the production of protective natural Abs (IgM, IgG) [ 42 , 43 ]. Interestingly, B2 lymphocytes can differentiate directly into B1 lymphocytes, and this process is controlled by a self-reactive B cell receptor [ 44 ].…”
Section: Diversity Of Abs Types: Antigen-specific Natural Polyrementioning
confidence: 99%
“…28,31 Indeed, work from the Barton laboratory shows that expansion of PtC-specific BCRs in the B1a compartment is regulated by endosomal TLRs that recognize nucleic acids. 44 Conversely, endosomal…”
Section: T H Y 1 -/ -H O S T / a T Amentioning
confidence: 99%